ChemInform Abstract: Rhodium‐Catalyzed Intramolecular [5 + 2] Cycloaddition of Inverted 3‐Acyloxy‐1, 4‐enyne and Alkyne: Experimental and Theoretical Studies. Issue 41 (September 2016) - Li, Xiaoxun; Song, Wangze; Ke, Xiaona; Xu, Xiufang; Liu, Peng; Houk, K. N.; Zhao, Xian‐liang; Tang, Weiping
Abstract: A new type of ACE, i.e.